KARAKTERISTIK AGRONOMI BEBERAPA VARIETAS BAWANG MERAH (Allium ascalonicum L.) DATARAN RENDAH - Ariani Syahfitri Harahap; Devi Andriani Luta dan Sri Mahareni Br Sitepu3 (PROSIDING, 2022)
The purpose of this study was to see the agronomy characteristics of several onion varieties (Allium ascalonicum L.). The study was conducted in Klambir Lima Village, Hamparan Perak District, Deli Serdang Regency, North Sumatra Province with an altitude of ± 25 meters above sea level above sea level. This study was conducted in January to April 2022. The research method used was the Random Design Group (Rack) of a single factor. These factors consist of 4 treatments, namely: Shallots Super Philips, Bauji, Bima Brebes and Maja Cipanas varieties. The parameters observed are plant height, number of puppies, number of leaves, number of tubers per sample, tuber diameter, wet weight of samples per sample, wet tubers per plot, dry weight of tubers per plot, leaf color and tuber color. The data obtained was analyzed using variety of analysis. If the analysis of the variety shows the real difference at α = 5% it will be continued with DMRT (Duncan Multiple Range Test). From the research results of the Bauji varieties of onion have advantages in several observation parameters compared to the onion of super philips, Bima Brebes and Maja Cipanas varieties. Keywords: Karakteristik, Agronomi, Bawang merah, Dataran rendah.